The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3164/jcbn.11-73
|View full text |Cite
|
Sign up to set email alerts
|

Nootropic activity of acetaminophen against colchicine induced cognitive impairment in rats

Abstract: Alzheimer’s disease is a devastating neurodegenerative disorder, the most common among the dementing illnesses. Acetaminophen has gaining importance in neurodegenerative diseases by attenuating the dopaminergic neurodegeneration in Caenorhabditis elegans model, decreasing the chemokines and the cytokines and increasing the anti apoptotic protein such as Bcl-2 in neuronal cell culture. The low concentration acetaminophen improved the facilitation to find the hidden platform in Morris Water Maze Test. Also some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Moreover, the gradual increase in impairment of the two parameters suggested a progressive nature for this impairment, a characteristic feature in AD. The findings here were in line with those of other investigators who showed that icv colchine injection of rats led to impaired memory in a Morris water maze (Kumar & Gupta, 2002;Kumar et al, 2007aKumar et al, , b, 2008Kumar et al, , 2010, a step-through passive avoidance apparatus (Pitchaimani et al, 2012) and a radial arm maze (Ganguly & Guha, 2008).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Moreover, the gradual increase in impairment of the two parameters suggested a progressive nature for this impairment, a characteristic feature in AD. The findings here were in line with those of other investigators who showed that icv colchine injection of rats led to impaired memory in a Morris water maze (Kumar & Gupta, 2002;Kumar et al, 2007aKumar et al, , b, 2008Kumar et al, , 2010, a step-through passive avoidance apparatus (Pitchaimani et al, 2012) and a radial arm maze (Ganguly & Guha, 2008).…”
Section: Discussionsupporting
confidence: 81%
“…The type of information gleaned from those types of studies may be useful to compare colchicine-induced neurodegeneration with that associated with other neurodegenerative diseases, such as Alzheimer's Disease (AD). A colchicine (icv)-induced neurodegeneration model has been considered by many as a sporadic model of AD on the basis of impairment of cognitive functions and loss of cholinergic neurons (Ganguly & Guha, 2008;Kumar et al, 2007a;Pitchaimani et al, 2012;Shigematsu & McGeer, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, a wide array of neuroprotective effects of APAP has been reported in different studies [24, 2729, 48]. Previous studies have shown that APAP can protect neurons from degeneration in animal models and cell lines of AD [29] and PD [49] that involves inflammatory and oxidative stress processes. Given the evidence that sepsis can cause cognitive impairment in human subjects [50, 51], our study focused on the effects of APAP in an LPS-induced cognitive impairment mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, APAP has been shown to protect dopaminergic neurons from oxidative damage evoked by acute exposure to 6-hydroxydopamine or excessive levels of dopamine in vitro [28], suggesting a potential benefit for PD. Finally, recent studies have shown that APAP shows nootropic activity through increasing the escape latency in the step through passive avoidance paradigm task and decreasing acetyl cholinesterase activity in colchicine-induced cognitive impairment (an animal model for AD) in rats [29], suggesting a possible therapeutic effect of APAP in AD.…”
Section: Introductionmentioning
confidence: 99%
“…The colchicine-induced model of neurodegeneration has been used by several authors as a model of SAD [28,29,30], but the exact mechanism of neurodegeneration in this model is not known. If neuroinflammation is related with neurodegeneration in the colchicine-induced AD model, then COX may play an important role in this process.…”
Section: Introductionmentioning
confidence: 99%